Are We More Sustainable Yet? Results of a Longitudinal Curriculum Study by Means of Topic-Based Indicators - Bagoly-Simó, Péter; Hartmann, Johanna (Journal of Geography Education, 2021)
In the context of ongoing efforts to measure the implementation of ESD into formal education, this paper aims to explore change pattern in implementation during curricular reform. Revisiting Bagoly-Simó’s (2013a, 2013b, 2014a) four indicators measuring depth and breadth of implementation, this study analyzed the 2017 Bavarian curriculum for Realschule. The results indicate a persisting trend of specialization and superficial ESD implementation with Geography, Science, and a few vocational subjects showing a more profound implementation. While shifts in ESD discourses require a continuous revision of ESD-topics, they remain of crucial in diagnosing the links between ESD and each school subject’s core knowledge.